Inflammatory Bowel Diseases in Children: Modern Achievements in Diagnostics and Therapy - A. I. Khavkin; A. V. Nalyotov; N. A. Marchenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to highlight current trends in the diagnosis and treatment of inflammatory bowel diseases in children.Key points. The incidence of inflammatory bowel disease among children has increased significantly over the past three decades. Moreover, these diseases are often characterized by a severe course. At the same time, strategies for diagnosing and treating these patients are being improved: doctors began using high-definition endoscopy and video capsule endoscopy, the determination of fecal calprotectin, biological therapy (infliximab, adalimumab, vedolizumab, and ustekinumab) and drug monitoring. Particular attention is paid to the role of dietary recommendations.Conclusion. Currently, there has been significant progress in the diagnosis and treatment of inflammatory bowel diseases in children.